Interleukin-6 prevents NMDA-induced neuronal Ca2+ overload via suppression of IP3 receptors. (August 2013) - Liu, Zhan; Fang, Xiao-Xia; Chen, Yu-Ping; Qiu, Yi-Hua; Peng, Yu-Ping
Abstract Primary objective: The mechanism underlying interleukin-6 (IL-6) prevention of N-methyl-D-aspartate (NMDA)-induced neuronal Ca2+ overload was explored at the profile of Ca2+ channel receptors, including NMDA, inositol 1, 4, 5-trisphosphate and ryanodine receptors (NMDAR, IP3R and RyR, respectively). Methods: Cerebellar granule neurons from 8-day-old rats were exposed to IL-6 (40 or 120 ng ml−1) for 8 days and stimulated with NMDA (100 μM) for 15 or 30 minutes. Results: NMDA evoked an acute and sustained enhancement of intracellular Ca2+ fluorescence intensity in the entire 15-minute NMDA application period. IL-6 prevented the acute and sustained intracellular Ca2+ elevation triggered by NMDA in a concentration-dependent manner. MK-801, an NMDAR antagonist, completely suppressed NMDA-evoked neuronal Ca2+ overload in the absence or presence of IL-6. IP3R antagonist 2-APB lessened NMDA-evoked acute and sustained cytosolic Ca2+ overload and IL-6 further reduced the acute 2-APB-dependent Ca2+ component. Dissimilarly, after RyR antagonist DAN treatment, NMDA still induced an acute and sustained elevation of intracellular Ca2+ levels, and the elevated Ca2+ was significantly suppressed by IL-6. Moreover, IL-6 down-regulated NMDAR1 and IP3R1 but did not alter RyR2 expression. Conclusion: The present results suggest that IL-6 suppresses NMDA-induced neuronal Ca2+ overload by inhibiting NMDAR and IP3R activities.